A UK reported case of Graves' disease with thyroid hemiagenesis. Issue 8 (2nd August 2019) - Faulkner, Jack; Varadharajan, Kiran; Choudhury, Natasha
Abstract : We present a rare case of a 31-year-old patient with Graves' disease with agenesis of the left thyroid lobe. The patient was managed with a right hemithyroidectomy and isthmusectomy as definitively treatment of Graves' disease. The patient had an uneventful postoperative outcome and the histology was benign and consistent with Graves' disease. This is a rare case in the literature of Graves' disease with unilateral thyroid agenesis, and to our knowledge is the first reported case from the UK.